Vibrational relaxation dynamics of the nitrogen-vacancy center in diamond - Ulbricht, Ronald (2018)
We employ a combination of spectrally resolved optical pump-probe spectroscopy and excited-state ab initio molecular dynamics (ESAIMD) simulations to study the ultrafast vibrational relaxation dynamics of the 3E excited state of negatively charged nitrogen vacancy (NV−) defects. The experimental results reveal vibrational relaxation in the phonon sideband with a time constant of approximately 50 fs, in excellent agreement with the ∼40-fs structural equilibration timescale predicted by ESAIMD simulations. The observed ultrafast vibrational energy relaxation implies that dynamical processes triggered by photoexcitation into the phonon sideband of the NV− center occur primarily in the lowest vibronic level of the 3E state.